Efficacy and safety of hemoporfin photodynamic therapy in treating port-wine stains in Chinese children: a systematic review and meta-analysis - Xu, Jing; Li, Hongxin (Frontiers in Pediatrics, 2025)
ObjectiveThe purpose of this study is to explore the efficacy and safety of hematoporphyrin monomethyl ether mediated photodynamic therapy (HMME-PDT) in treating children with port-wine stains (PWS).MethodLiterature related to the topic was searched in PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure, Wanfang, and China Science Technology Journal Database online databases. The quality of the literature was evaluated using the Effective Public Health Practice Project. The I2 statistic was used to evaluate the consistency of the results.ResultsA total of 19 papers were included. Meta-analysis showed that more than half of the children (56.3%) achieved efficacy I (improvement ≥ 60%). 17% of children achieved efficacy II (improvement ≥ 75%). Regardless of whether the outcome variable was efficacy I or efficacy II, the therapeutic efficacy in children with PWS aged 0–3 years was superior to those aged 3–6 and 6–18 years, and children who underwent a treatment course of ≥3 sessions showed better outcomes compared to those who have only 1 or 2 sessions. After treatment with HMME-PDT, better efficacy was seen in the PWS of the face and neck and pink/red PWS. Additionally, almost all children with PWS treated with HMME-PDT developed edema (99.9%), more than half presented purpura (67.6%), some developed crust (30.8%) and hyperpigmentation (15.0%), and a few occurred scar (2.4%) and hypopigmentation (1.4%).ConclusionAfter HMME-PDT treatment, more than half of the pediatric patients showed an improvement of ≥60%, and no serious adverse reaction events occurred. This study demonstrated that HMME-PDT possessed promising therapeutic efficacy in children with PWS, suggesting that HMME-PDT could be considered a recommended treatment strategy for pediatric PWS. However, future development of standardized assessment guidelines and comparative studies are needed to validate the aforementioned conclusions.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/#loginpage, PROSPERO (CRD42024592367).